Ship transportation [electronic resource] - Ketchum, H. G. C. (Henry George Clopper), 1839-1896.; Ketchum, H. G. C. (Henry George Clopper), 1839-1896. The Chignecto Ship Railway; Canadian Society of Civil Engineers. ([S.l. : s.n., 1891)
With: The Chignecto Ship Railway: the substitute for the Baie Verte Canal / by H.G.C. Ketchum. Caption title. At head of title: Advance proof . Canadian Society of Civil Engineers, incorporated 1887. Transactions . "To be read Tuesday, 29th December, 1891." Electronic reproduction. Mode of access: Internet. 44